The Social and Behavioral Sciences in K-12 Education: Past, Present, and Future: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The ability to meet many of society’s challenges requires an understanding of human behavior. From health to education to business to homeland security, the social and behavioral sciences (SBS)—which include psychology, political science, economics, anthropology, and sociology—contribute to solving important problems for individuals, organizations, and society. Although they are taught widely at the university level, they have far less presence in K-12 education where students’ core knowledge is shaped.
Keywords: Education

Increasing the Roles and Significance of Teachers in Policymaking for K-12 Engineering Education: Proceedings of a Convocation - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Engineering is a small but growing part of K–12 education. Curricula that use the principles and practices of engineering are providing opportunities for elementary, middle, and high school students to design solutions to problems of immediate practical and societal importance. Professional development programs are showing teachers how to use engineering to engage students, to improve their learning of science, technology, engineering, and mathematics (STEM), and to spark their interest in engineering careers. However, many of the policies and practices that shape K–12 engineering education have not been fully or, in some cases, even marginally informed by the knowledge of teacher leaders.
Keywords: Education

Protecting the Health and Well-Being of Communities in a Changing Climate: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On March 13, 2017, the Roundtable on Environmental Health Sciences, Research, and Medicine and the Roundtable on Population Health Improvement held a 1-day public workshop at the National Academy of Sciences building in Washington, DC. Participants discussed regional, state, and local efforts to mitigate and adapt to health challenges arising from climate change, ranging from heat to rising water. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Environment and Environmental Studies

Lessons Learned from Diverse Efforts to Change Social Norms and Opportunities and Strategies to Promote Behavior Change in Behavioral Health: Proceedings of Two Workshops - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
In 2015, the National Academies of Sciences, Engineering, and Medicine convened two workshops with oversight from the Committee on the Science of Changing Behavioral Health Social Norms. The workshops provided input to the committee’s deliberations and contributed to the development of the report Ending Discrimination against People with Mental and Substance Use Disorders. That report was issued to help the Substance Abuse and Mental Health Services Administration and the Office of the Assistant Secretary for Planning and Evaluation, U.S. Department of Health and Human Services, utilize the scientific evidence base in improving public attitudes toward and understanding of behavioral health, specifically in the areas of mental health and substance use disorders. This publication summarizes the presentations and discussions at the two workshops.
Keywords: Behavioral and Social Sciences

Antarctic Sea Ice Variability in the Southern Ocean-Climate System: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The sea ice surrounding Antarctica has increased in extent and concentration from the late 1970s, when satellite-based measurements began, until 2015. Although this increasing trend is modest, it is surprising given the overall warming of the global climate and the region. Indeed, climate models, which incorporate our best understanding of the processes affecting the region, generally simulate a decrease in sea ice. Moreover, sea ice in the Arctic has exhibited pronounced declines over the same period, consistent with global climate model simulations. For these reasons, the behavior of Antarctic sea ice has presented a conundrum for global climate change science.
Keywords: Earth Sciences

Engineering Societies and Undergraduate Engineering Education: Proceedings of a Workshop - National Academy of Engineering (The National Academies Press, 2017)
Engineering professional societies in the United States are engaged in a wide range of activities involving undergraduate education. However, these activities generally are not coordinated and have not been assessed in such a way that information about their procedures and outcomes can be shared. Nor have they been assessed to determine whether they are optimally configured to mesh with corresponding initiatives undertaken by industry and academia. Engineering societies work largely independently on undergraduate education, leaving open the question of how much more effective their efforts could be if they worked more collaboratively—with each other as well as with academia and industry. To explore the potential for enhancing societies’ role at the undergraduate level, the National Academy of Engineering held a workshop on the engagement of engineering societies in undergraduate engineering education. This publication summarizes the presentations and discussions from the workshop.
Keywords: Engineering and Technology

Demographic Effects of Girls' Education in Developing Countries: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Educating girls is a universally accepted strategy for improving lives and advancing development. Girls’ schooling is associated with many demographic outcomes, including later age at marriage or union formation, lower fertility, and better child health. However, the causal pathways between education and demographic outcomes are not well understood.
Keywords: Education; Behavioral and Social Sciences

Future Financial Economics of Health Professional Education: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
An adequate, well-trained, and diverse health care workforce is essential for providing access to quality health care services. However, despite more than a decade of concerted global action to address the health workforce crisis, collective efforts are falling short in scaling up the supply of health workers. The resulting health workforce shortage affects people’s access to quality health care around the globe.
Keywords: Health and Medicine; Industry and Labor; Education

Exploring the Role of Accreditation in Enhancing Quality and Innovation in Health Professions Education: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The purpose of accreditation is to build a competent health workforce by ensuring the quality of training taking place within those institutions that have met certain criteria. It is the combination of institution or program accreditation with individual licensure—for confirming practitioner competence—that governments and professions use to reassure the public of the capability of its health workforce. Accreditation offers educational quality assurance to students, governments, ministries, and society.
Keywords: Health and Medicine; Education

Strategies to Limit Sugar-Sweetened Beverage Consumption in Young Children: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On June 21–22, 2017, the National Academies of Sciences, Engineering, and Medicine's Food and Nutrition Board convened a workshop in Washington, DC, to explore the range of policies and programs that exist at the federal, state, tribal, and local levels to limit sugar-sweetened beverage consumption in children birth to 5 years of age. Topics examined over the course of the 1.5-day workshop included prevalence and trends in beverage intake among young children; beverage intake guidelines applicable to the age range of interest; challenges and opportunities of influencing beverage consumption; the role of industry in beverage intake; and knowledge gaps and research needs. This publication summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition

Accomplishments of the U.S. Global Change Research Program - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The U.S. Global Change Research Program (USGCRP) is an interagency program, established by the Global Change Research Act (GCRA) of 1990, mandated by Congress to "assist the Nation and the world to understand, assess, predict, and respond to human-induced and natural processes of global change". Since the USGCRP began, scientific understanding of global change has increased and the information needs of the nation have changed dramatically.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies; Earth Sciences

Strategies to Limit Sugar-Sweetened Beverage Consumption in Young Children: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On June 21–22, 2017, the National Academies of Sciences, Engineering, and Medicine’s Food and Nutrition Board convened a workshop in Washington, DC, to explore the range of policies and programs that exist at the federal, state, tribal, and local levels to limit sugar-sweetened beverage consumption in children birth to 5 years of age. Topics examined over the course of the 1.5-day workshop included prevalence and trends in beverage intake among young children; beverage intake guidelines applicable to the age range of interest; challenges and opportunities of influencing beverage consumption; the role of industry in beverage intake; and knowledge gaps and research needs. This publication highlights key points made by individual speakers during the presentations and discussions.
Keywords: Food and Nutrition; Health and Medicine

Sustaining Ocean Observations to Understand Future Changes in Earth's Climate - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The ocean is an integral component of the Earth's climate system. It covers about 70% of the Earth's surface and acts as its primary reservoir of heat and carbon, absorbing over 90% of the surplus heat and about 30% of the carbon dioxide associated with human activities, and receiving close to 100% of fresh water lost from land ice. With the accumulation of greenhouse gases in the atmosphere, notably carbon dioxide from fossil fuel combustion, the Earth's climate is now changing more rapidly than at any time since the advent of human societies. Society will increasingly face complex decisions about how to mitigate the adverse impacts of climate change such as droughts, sea-level rise, ocean acidification, species loss, changes to growing seasons, and stronger and possibly more frequent storms. Observations play a foundational role in documenting the state and variability of components of the climate system and facilitating climate prediction and scenario development. Regular and consistent collection of ocean observations over decades to centuries would monitor the Earth's main reservoirs of heat, carbon dioxide, and water and provides a critical record of long-term change and variability over multiple time scales. Sustained high-quality observations are also needed to test and improve climate models, which provide insights into the future climate system. Sustaining Ocean Observations to Understand Future Changes in Earth's Climate considers processes for identifying priority ocean observations that will improve understanding of the Earth's climate processes, and the challenges associated with sustaining these observations over long timeframes.
Keywords: Earth Sciences

An Assessment of ARPA-E: Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
In 2005, the National Research Council report Rising Above the Gathering Storm recommended a new way for the federal government to spur technological breakthroughs in the energy sector. It recommended the creation of a new agency, the Advanced Research Projects Agency-Energy, or ARPA-E, as an adaptation of the Defense Advanced Research Projects Agency (DARPA) model—widely considered a successful experiment that has funded out-of-the-box, transformative research and engineering that made possible the Internet, GPS, and stealth aircraft. This new agency was envisioned as a means of tackling the nation’s energy challenges in a way that could translate basic research into technological breakthroughs while also addressing economic, environmental, and security issues.
Keywords: Policy for Science and Technology

Review of the Draft Climate Science Special Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The United States Global Change Research Program (USGCRP) is moving towards a sustained assessment process that allows for more fluid and consistent integration of scientific knowledge into the mandated quadrennial National Climate Assessment. As part of this process, the USGCRP is developing the Climate Science Special Report (CSSR), a technical report that details the current state-of-science relating to climate change and its physical impacts. The CSSR is intended to focus on climate change in the United States and to inform future USGCRP products.
Keywords: Earth Sciences

Valuing Climate Damages: Updating Estimation of the Social Cost of Carbon Dioxide - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The social cost of carbon (SC-CO2) is an economic metric intended to provide a comprehensive estimate of the net damages - that is, the monetized value of the net impacts, both negative and positive - from the global climate change that results from a small (1-metric ton) increase in carbon-dioxide (CO2) emissions. Under Executive Orders regarding regulatory impact analysis and as required by a court ruling, the U.S. government has since 2008 used estimates of the SC-CO2 in federal rulemakings to value the costs and benefits associated with changes in CO2 emissions. In 2010, the Interagency Working Group on the Social Cost of Greenhouse Gases (IWG) developed a methodology for estimating the SC-CO2 across a range of assumptions about future socioeconomic and physical earth systems. Valuing Climate Changes examines potential approaches, along with their relative merits and challenges, for a comprehensive update to the current methodology. This publication also recommends near- and longer-term research priorities to ensure that the SC- CO2 estimates reflect the best available science.
Keywords: Environment and Environmental Studies

Engineering Technology Education in the United States - National Academy of Engineering (The National Academies Press, 2017)
The vitality of the innovation economy in the United States depends on the availability of a highly educated technical workforce. A key component of this workforce consists of engineers, engineering technicians, and engineering technologists. However, unlike the much better-known field of engineering, engineering technology (ET) is unfamiliar to most Americans and goes unmentioned in most policy discussions about the US technical workforce. Engineering Technology Education in the United States seeks to shed light on the status, role, and needs of ET education in the United States.
Keywords: Engineering and Technology; Education

Long-Term Pavement Performance and Long-Term Bridge Performance Committees Joint Letter Report: March 14, 2017 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On March 14, 2017, TRB’s Long-Term Pavement Performance (LTPP) Committee and Long-Term Bridge Performance (LTBP) Committee sent a joint letter report to Walter C. "Butch" Waidelich, Jr., acting deputy administrator of the Federal Highway Administration (FHWA), and Frederick G. "Bud" Wright, executive director of the American Association of State Highway and Transportation Officials (AASHTO). The report addresses reductions in funding for research, development, and technology in the Fixing America's Surface Transportation (FAST) Act and the implications for the LTPP and LTBP programs. In response to a joint meeting held at the request of FHWA, the committees make recommendations to preserve the essential elements of the LTPP and LTBP programs, on future areas of emphasis for the two programs, possible alternate sources of supplemental funding, and possible areas for enhancing program efficiency.
Keywords: Transportation and Infrastructure

Optimizing Strategies for Clinical Decision Support: Summary of a Meeting Series - National Academy of Medicine (The National Academies Press, 2017)
As a result of a collaboration between the National Academy of Medicine (NAM) and the Office of the National Coordinator for Health Information Technology, this NAM Special Publication summarizes and builds on a meeting series in which a multi-stakeholder group of experts discussed the potential of clinical decision support (CDS) to transform care delivery by ameliorating the burden that expanding clinical knowledge and care and choice complexity place on the finite time and attention of clinicians, patients, and members of the care team. This summary also includes highlights from discussions to address the barriers to realizing the full benefits of CDS-facilitated value improvement. Optimizing Strategies for Clinical Decision Support identifies the need for a continuously learning health system driven by the seamless and rapid generation, processing, and practical application of the best available evidence for clinical decision making and lays out a series of actionable collaborative next steps to optimize strategies for adoption and use of CDS.
Keywords: Health and Medicine

Accelerating Medical Evidence Generation and Use: Summary of a Meeting Series - National Academy of Medicine (The National Academies Press, 2017)
In 2016, the National Academy of Medicine (NAM) hosted a series of meetings, which was sponsored by the Patient-Centered Outcomes Research Institute, with support from NAM's Executive Leadership Network. The series underscored the importance of partnerships between researchers and health system leadership and considered opportunities to build institutional capacity, cross-institutional synergy, and system-wide learning. During these meetings, health system executives, researchers, and others discussed building infrastructure that simultaneously facilitates care delivery, care improvement and evidence development. The vision is a digital system-wide progress toward continuous and seamless learning and improvement throughout health and health care. This publication aims to answer the following questions:How can evidence development be accelerated, given current knowledge and resources?What might that mean for better outcomes for patients and greater efficiency in health care?What system and culture changes are required to generate evidence from the care experience?How much progress has been made in preparing the field for the paradigm shift?What are the hallmarks of successful partnerships among care executives and research leaders?What are the priorities in advancing executive leadership to the next level for continuously learning health and health care?
Keywords: Health and Medicine